Analysis of the Impact of Population Policy on Criminality and Individual Security in the New Normal Era in Makassar City - Anwar Parawangi; Nur Wahid; Nurbiah Tahir; Rusliadi Rusliadi; Nurul Anisa Handayani (Program Pascasarjana Universitas Negeri Makassar, 2024)
Crimes cannot be separated from personal security and are a serious threat to the security and welfare of society. This study aims to determine the relationship between the impact of population, poverty and individual security and crime in Makassar City. The method used in this research is a qualitative method using a normative descriptive approach. The data collection in this research is through observation, interviews and documents. Then the data is analysed by researchers to get the best conclusion. The result of this research is the analysis of the impact of population on crime and individual security is becoming increasingly relevant and important. High population density in an area can place pressure on resources and infrastructure, creating an environment that is less safe and prone to crime. High population density can increase economic competition, create social instability, and complicate law enforcement.